Perancangan dan Evaluasi User Experience Aplikasi Microteaching Pendukung Standar Kompetensi Mahasiswa Calon Guru berbasis Mobile dengan Pendekatan Human Centered Design dan Remote Usability Testing - Anak Agung Adi Wiryya Putra; Retno Indah Rokhmawati; Hanifah Muslimah Az-Zahra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Design and Evaluation of User Experience for Microteaching Applications with Mobile-Based to Support Competency Standards for Educational Students With Human Centered Design Approaches and Remote Usability Testing is carried out with the aim of supporting the achievement of competency standards for prospective teacher students through the design of applications that are used to reflect microteaching activities. The approach used in the design is Human Centered Design, while the methods used in testing are Remote Usability Testing and Retrospective Think Aloud. The research method used in this study is qualitative research with activities to collect data, analyze data, and finally obtain information related to the results of processing the data. The participants involved in this study were 6 people consisting of lecturers in micro learning courses, vocational teachers, and students of the Information Technology Education Study Program. Based on the effectiveness test by calculating the success rate has a success rate of 95.2%. Based on the results of calculations with time based efficiency, the efficiency value is 0.155 goals/second. In the aspect of ease of use, the score is 6.76 with a Single Ease Question (SEQ) measurement which indicates that the microteaching application can be categorized as an application that is very easy to use. Improvements were made to the splash screen and homepage pages that were more directed at improving the appearance, clarifying buttons, and also eliminating buttons that did not have functions to make it easier for users.